Desert Plants Leaf-surface Wax as Eco-friendly Lubricant Additive for an Aluminumon- steel Contact - Xia, Yanqiu; Zhao, Shengguang; Feng, Xin (Journal of Environmental Accounting and Management, 2026)
The friction behavior of leaf-surface wax of two desert plants, Ammopiptanthus mongolicus and Reaumuria soongorica, as additives were evaluated on an aluminum-on-steel system, glycerol and molybdenum-dithiocarbamate (MoDTC) as compaire additive. A Gas chromatography-mass spectrometry (GC-MS) analysis system was performed to identify the composition of Ammopiptanthus mongolicus leaf wax. Scanning electron microscopy and X-ray photoelectron spectroscopy(XPS) were employed to explore the friction mechanisms of Ammopiptanthus mongolicus leaf-surface wax. The poly-alpha-olefin (PAO) containing leaf-surface wax showed a better friction reducing and wear resistance properties than that of containing glycerol and MoDTC, respectively. The results show that the leaf-surface wax of desert plants could effectively reduce the friction and wear of aluminum-on-steel sliding pairs compared with the PAO containing MoDTC, and glycerol as additives. Especially, Ammopiptanthus mongolicus showed high performance anti-wear and friction reducing properties. The excellent tribological properties were attributed to the wax composition of leafsurface fatty acid, alcohol, and esters.